The comparison between subjective and objective free-living physical activity in women with diverse weight loss histories - Burrows, Robyn Toni (Department of Human Biology, 2024)
Introduction: Weight regain following weight loss is a universal concern for successful obesity management strategies. The tendency evident in reduced-weight women to overestimate physical activity may be one of the causes of unsuccessful weight loss maintenance in the long term. The current study aimed to 1) identify differences in objective (accelerometry) and self-reported (GPAQ) free-living physical activity in women who experienced weight loss, and 2) determine whether overor-underestimation of physical activity was related to time at goal weight. Methods: Reduced-obese women (n = 19) were recruited for this study. The reduced-obese condition consisted of women who had lost a minimum of 10% of their body weight 18-6 months before testing. Prior to visiting the laboratory, participants were telephonically questioned to determine their inclusion or exclusion status for the study. During the first visit, participants completed physical assessments (BMI, body fat percentage), the Global Physical Activity Questionnaire (GPAQ), and underwent the accelerometer fitting. The accelerometer was worn for a period of 7 days and was used to measure free-living daily activity. Means ± SD were used to analyse parametric data and medians and interquartile range were used to assess non-parametric data. Pearson correlations were used to measure the association between the two methods. Paired sample t-tests, Chi-square tests and Effect sizes using Cohen's d were run. Finally, we visually inspected and statistically tested the results using Bland-Altman plots and simple liner regressions. Results: On average, participants lost 23.3  9.1 percent of their weight over an average period of 7  2.8 months. Participants underestimated their sedentary time and time spent in moderate-intensity activity and overestimated their vigorous-intensity activity. Bland-Altman plots revealed a proportional bias for time spent per day in sedentary time, vigorous-intensity activity, and MVPA. MVPA showed a statistically significant positive correlation between the two measures, r = 0.72, p = 0.0006. Time spent in moderate activity showed the best agreement between the self-reported measure and accelerometry, revealing no proportional bias (mean SD bias of -61.8 38.2 min per day). Chi-squared results revealed that 11 participants (of which 9 were at their goal weight for 6 months and 2 were at their goal weight for longer than 6 months) underestimated their MVPA. Chisquared results also revealed that 7 participants (of which 6 were at their goal weight for 6 months and 1 was at their goal weight for longer than 6 months) overestimated their vigorous-intensity activity. Discussion and conclusion: Underestimation of sedentary time and overestimation of vigorous intensity exercise put the group of reduced-obese women at risk for weight regain in the long term. The moderate-intensity activity was largely underreported, which requires further investigation. It is imperative that research on reduced-weight women make use of objective measures for the measurement of free-living activity, for self-reported measures will lead to a misinterpretation of this specific population's physical activity status.